Uncovering Differences in Virulence Markers Associated with Achromobacter Species of CF and Non-CF Origin - Filipic, Brankica; Malesevic, Milka; Vasiljevic, Zorica; Lukic, Jovanka; Novovic, Katarina; Kojic, Milan; Jovcic, Branko (Frontiers in Cellular and Infection Microbiology, 2017)
Achromobacter spp. are recognized as emerging pathogens in hospitalized as well as in cystic fibrosis (CF) patients. From 2012 to 2015, we collected 69 clinical isolates (41 patient) of Achromobacter spp. from 13 patients with CF (CF isolates, n=32) and 28 patients receiving care for other health conditions (non-CF isolates, n=37). Molecular epidemiology and virulence potential of isolates were examined. Antimicrobial susceptibility, motility, ability to form biofilms and binding affinity to mucin, collagen and fibronectin were tested to assess their virulence traits. The nrdA gene sequencing showed that A. xylosoxidans was the most prevalent species in both CF and non-CF patients. CF patients were also colonized with A. dolens/A. ruhlandii, A. insuavis and A. spiritinus strains while non-CF group was somewhat less heterogenous, although A. insuavis, A. insolitus and A. piechaudii strains were detected beside A. xylosoxidans. Three strains displayed clonal distribution, one among patients from the CF group and two among non-CF patients. No significant differences in susceptibility to antimicrobials were observed between CF and non-CF patients. About one third of the isolates were classified as strong biofilm producers, and the proportion of CF and non-CF isolates with the ability to form biofilm was almost identical. CF isolates were less motile compared to the non-CF group and no correlation was found between swimming phenotype and biofilm formation. On the other hand, CF isolates exhibited higher affinity to bind mucin, collagen and fibronectin. In generall, CF isolates from our study exhibited in vitro properties that could be of importance for the colonization of CF patients.